Net power production & performance at different stroke rates & abilities during sculling - Smith, R.; Loschner, C. (coachesinfo.com, 2000)
Rowers studied in this project according their work effectiveness over four stroke rates spanning cadences of 20-30. The paper examines the relationship between patterns of power production and absorption and the velocity of the boat.